PHYSIOLOGICAL, GENOMIC AND PRESERVATIVE PROPERTIES OF PEDIOCOCCUS ISOLATES FROM MEATS UNDER LOW TEMPERATURE STORAGE (2012)
The need for meat preservation cannot be overemphasised. However, existing methods of meat preservation including the use of artificial preservatives have toxic side effects. There is a dearth of information on the use of Lactic Acid Bacteria (LAB), which is known as good preservatives for food, in the preservation of meat. Hence, the aim of this study was to examine the use of Pediococcus acidilactici and low temperature in improving the quality of beef, chicken and turkey meat samples. Samples of beef, chicken and turkey were obtained from open market retailers and stored for 28 days at 4oC, 2oC, -4oC and -15oC. From these, LAB were isolated and identified using conventional methods. Quantities of lactic acid and acetic acid were determined using high performance liquid chromatography, while diacetyl and hydrogen peroxide were determined by enzymatic methods. High production of lactic acid was used as a criterion for selecting five isolates of Pediococcus acidilactici and the 16S rDNA genes were amplified and sequenced. The isolates were checked for plasmid presence and tested for bacteriocin production using gel electrophoresis and agar well assay. Antimicrobials produced by the isolates were tested in vitro against known meat spoilage organisms: Staphylococcus aureus, Escherichia coli, Pseudomonas faecalis, Listeria monocytogenes, Salmonella typhimurium and Bacillus cereus. The isolates and their filtrates were applied to fresh meat at -4oC and -15oC. Microbial load, proximate and biochemical parameters of the meat samples were monitored at seven days interval for 28 days. Data were analysed using ANOVA at p = 0.05. One hundred and ten LAB isolates from beef [Lactobacillus (24), Pediococcus (6), Leuconostoc (9)], chicken [Lactobacillus (27), Pediococcus (4), Leuconostoc (2)] and turkey [Lactobacillus (31), Pediococcus (5), Leuconostoc 2] were identified. Fast freezing (-15oC) and freezing (-4oC) gave significantly lower LAB count (4.1 ± 0.03 - 5.1 ± 0.02 logcfu/mL) than those of chilling (2oC) and refrigeration (4oC) (4.2 ± 0.04 - 5.4 ± 0.02 logcfu/mL) in all the meat samples. Lactic acid and acetic acid production peaked at 30.7 g/L and 32.0 mg/mL respectively while diacetyl and hydrogen peroxide production peaked at 40.8 ng/L and 16.0 µg/L respectively. Sizes of the 16S rDNA from the five strains of P. acidilactici ranged from 145 bp to 161 bp. Band size of plasmid DNA ranged from 861 - 20643 bp. Bacteriocin inhibition zones ranged from 1.0 to 6.5 mm. The highest zone of inhibition of antimicrobial action was 12 mm against P. faecalis. Proximate and biochemical analyses gave lower values compared with control samples: pH (4.8 / 5.7), thiobarbituric acid (0.2 / 0.5 mg malonaldehyde/kg), free fatty acid (0. 2 / 0.5 KOH/g lipid), total volatile nitrogen (0.6 / 1.4 mgN/100) and crude fat (3.4 / 4.5 %); but increased crude protein (22.1 / 17.7 %). Lowest microbial load (total bacteria count 2.2 logcfu/ml, coliform count 1.4 logcfu/ml, fungal count 2.0 logcfu/ml) and highest LAB count (4.9 logcfu/ml) were observed on the 28th day. Pediococcus acidilactici with optimum physiological characteristics prolonged the keeping quality of meat under low temperature storage.